DEVELOPING ENGLISH SUMMATIVE TEST BASED ON REVISED BLOOM’S TAXONOMY - Theresia Manalu and Indra Hartoyo (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2016)
This was a research and development (R&D) study which aimed to evaluate the English summative test items based on revised Bloom’s taxonomy for grade VIII. This study focused on the developing the English summative test items according to the cognitive level of revised Bloom’s taxonomy for grade VIII at SMP Negeri 3 Tebing Tinggi. The data consist of the existing English summative test items which were directly collected from the English teacher due to analyze the proportion of cognitive level according to revised Bloom’s taxonomy. Based on the data analysis, the existing English summative test had not fulfilled the proportion of cognitive level according to revised Bloom’s taxonomy regulated by the Ministry of Education and Culture. The inappropriate English summative test items were then developed according to the proportion demand and suitability to the syllabus and indicators. The results of the study are 30 developed English summative test items which had been validated by the experts and tested to 20 students due to get the reliability scores.